Ryan's Ballistic Trauma A Practical Guide - Brooks, Adam J.; Clasper, Jon; Midwinter, Mark; Hodgetts, Timothy J.; Mahoney, Peter F. (Springer London : Imprint: Springer, 2011)
Ryan's Ballistic Trauma 3rd Edition provides a concise guide to the clinical and operational issues surrounding the management of the ballistic casualty. This book crystallizes the knowledge and experience accrued by those dealing with ballistic trauma on a regular basis and extends this to those who have to manage these patients on an occasional basis only. Ryan's Ballistic Trauma 3rd Edition is a valuable reference tool for all medical and paramedical personnel involved in the care of patients with ballistic injury. It is especially relevant for consultants and senior trainees in surgery, anesthesia and emergency medicine who are likely to be involved in the management of these unique injuries. This book is essential reading for pre-hospital care providers and nurses working in the emergency room, as well as military surgeons and medical and nursing staff on deployment in regions of conflict.